Knowledge, attitude, and acceptance of healthcare workers and the public regarding the COVID-19 vaccine: a cross-sectional study - Muhammed Elhadi; Ahmed Alsoufi; Abdulmueti Alhadi; Amel Hmeida; Entisar Alshareea; Mawadda Dokali; Sanabel Abodabos; Omaymah Alsadiq; Mohammed Abdelkabir; Aimen Ashini; Abdulhamid Shaban; Saja Mohammed; et al. (BMC, 2021)
Abstract Background This study determined the knowledge, attitudes, and practice regarding COVID-19 and assessed the acceptance of the COVID-19 vaccine among healthcare workers and the general population. Methods A web-based, cross-sectional study was conducted using convenience sampling in Libya from December 1 to 18, 2020 among the general population and healthcare workers. Data on demographic characteristics, COVID-19 vaccination-related concerns, knowledge, attitudes, and practice regarding COVID-19, and knowledge, attitudes, and acceptance regarding the COVID-19 vaccine were collected using a self-administered survey. A binomial logistic regression was performed with 70% efficacy to determine the association between acceptance of the vaccine and study variables. Results Valid and complete responses were collected from 15,087 participants. Of these, 6227 (41.3%) were male and 8860 (58.7%) were female, with a mean (SD) age of 30.6 ± 9.8 years. Moreover, 485 (3.2%) participants were infected with COVID-19 at the time of the study, while 2000 (13.3%) had been previously infected. Overall, 2452 (16.3%) participants agreed, and 3127 (20.7%) strongly agreed, with "having concerns about serious vaccine-related complications." Mask-wearing adherence was reported by 10,268 (68.1%) of the participants. Most participants (14,050, 93.1%) believed that the vaccine should be provided for free, while 7272 (48.2%) were willing to buy it. Regarding vaccine acceptance and efficacy, 12,006 (79.6%) reported their willingness to take the vaccine with an efficacy of 90% or more, 9143 (60.6%) with an efficacy of 70% or more, and only 6212 (41.2%) with an efficacy of 50%. The binomial logistic regression revealed that vaccine acceptance was not associated with belonging to the medical field versus the general population. Acceptance was statistically associated with younger age groups, especially 31-40 (OR = 1.3 [1.09, 1.55]) and 41-50 years (OR = 1.29, [1.09, 1.54]). However, having a family member or friend infected with COVID-19 was positively associated with the likelihood of vaccine acceptance (OR = 1.09 [1.02, 1.18]), while having a friend or family member who died due to COVID-19 was negatively associated with it (OR = 0.89 [0.84, 0.97]). Conclusions Acceptance of the COVID-19 vaccine is an essential determinant of vaccine uptake and the likelihood of controlling the COVID-19 pandemic. Developing strategies to decrease public hesitation and increase trust is vital for implementing vaccination programs.